How to make a silk purse from a sow's ear--a comprehensive review of strategies to optimise data for corrupt managers and incompetent clinicians. - Pitches, D; Burls, A; Fry-Smith, A (2003)
The introduction of performance league tables for UK surgeons and hospitals has forced them to learn how to present data in the best possible light. Though there is an urgent need for guidance, official guidelines on how to optimise performance data are lacking.